Effects of Serum From Radiofrequency Ablation Patients Receiving General Anesthesia or Local Anesthesia on Hepatocellular Carcinoma Cancer Cell Malignancy: A Prospective Randomized Controlled Trial - Shi, Yumiao; Wu, Tong; Wang, Tao; Liu, Yan; Wang, Xiaoqiang; Luo, Jiamei; Su, Diansan; Zhai, Bo; Tian, Jie (Frontiers in Oncology, 2021)
Abstract Background: Whether anesthesia methods affect malignant biological behavior of cancer remains unresolved. In this study, we aim to compare the effects of general anesthesia (GA) and local anesthesia (LA) on serum collected from primary hepatocellular carcinoma (HCC) patients presenting for radiofrequency ablation (RFA). Methods: From August 2020 to December 2020, a prospective, randomized, and controlled study was conducted at Renji Hospital, which is affiliated with Shanghai Jiaotong University School of Medicine. 25 qualified patients from 18 to 65 years of age undergoing RFA were enrolled in the study and randomly assigned into two groups: the GA group (n = 14) and the LA group (n = 11). Venous blood was drawn from all patients preoperatively and 1 hour postoperatively. The serum collected was then used for the culturing of HepG2 cells. The malignant biological behaviors of HepG2 cells, including invasion, migration and proliferation, were observed after 24 hours of exposure to patients’ serum. ELISA was used to compare expression levels of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) and lymphokines (IFN-γ, IL-2) in patients’ serum from both groups. Results: HepG2 cells cultured with postoperative serum obtained from patients who received GA, but not LA, were associated with significantly increased cell invasion, migration and proliferation, compared to preoperative serum from the same patient group. Expression levels of pro-inflammatory cytokines were significantly higher, and lymphokines significantly lower in postoperative serum from GA patients compared to the corresponding preoperative serum. Conclusion: GA affects the serum milieu of patients with HCC, promoting the malignant biological behavior of a human HCC cell line.